2015
DOI: 10.1038/bjc.2015.338
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α is involved in the expansion of CXCR4-positive cancer stem-like cells in renal cell carcinoma

Abstract: Background:Hypoxia and the subsequent activation of hypoxia-inducible factor-2α (HIF2α) contribute to the progression of a variety of cancers. However, their role in the generation of renal cell carcinoma-derived stem cells has not been fully addressed.Methods:A sphere formation assay, cell proliferation, RT–PCR, western blot, FACS, immunohistochemistry and tumour xenograft were used to study the role of HIF2α.Results:Propagation of four renal cell carcinoma (RCC) cell lines (Caki-1, Caki-2, 786-O, 769-P) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 39 publications
(43 reference statements)
2
28
1
Order By: Relevance
“…A number of differentially expressed genes in the Caki-1 cell line can be found in Supplementary Table S1. For example, chemokine receptor CXCR4 was reported to be 2.01-fold upregulated in the Caki-1 cell line; this was previously reported as a cancer stem cell marker, and CXCR4-positive cells exhibit great resistance to tyrosine kinase inhibitors (27,42,47). In addition, CXCR4 expression has significant prognostic value and therapeutic importance in RCC patients (13).…”
Section: Discussionmentioning
confidence: 90%
“…A number of differentially expressed genes in the Caki-1 cell line can be found in Supplementary Table S1. For example, chemokine receptor CXCR4 was reported to be 2.01-fold upregulated in the Caki-1 cell line; this was previously reported as a cancer stem cell marker, and CXCR4-positive cells exhibit great resistance to tyrosine kinase inhibitors (27,42,47). In addition, CXCR4 expression has significant prognostic value and therapeutic importance in RCC patients (13).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies demonstrate CXCR4 to be present only in a subpopulation of RCC cells that were more tumorigenic (42) and to enhance cell migration and wound healing of renal cancer cells (43). In vivo , RCC derived spheres developed into tumors and interestingly, expressed high levels of CXCR4 (44). Taken together, we speculate that VCAN can thus promote ccRCC progression and metastases by supporting a suitable ECM environment where MMP7 is activated leading to proteolytic VCAN fragments and CXCR4 induction.…”
Section: Discussionmentioning
confidence: 99%
“…Most of this evidence is based on tumor-tissue-specific SCLCCs, while some are based on RCC cell lines [1820, 42, 43]. SCLCCs have been identified from RCC cell lines based on chemokine receptor CXCR4 [19, 42] and side population cell selection by aldehyde dehydrogenase activity [18, 20, 43], Hoechst 33342 dye [44] and rhodamine 123 [45]. Previously, Bussolati et al observed renal carcinoma specimens from patients after radical nephrectomy, which showed CD105+ subpopulation is enrich for tumor-initiating cells (TICs) [31] and tumor angiogenesis [46].…”
Section: Discussionmentioning
confidence: 99%